Catch them young: Impact of financial socialization, financial literacy and attitude towards money on financial well‐being of young adults. (31st March 2020) - Utkarsh,; Pandey, Asheesh; Ashta, Arvind; Spiegelman, Eli; Sutan, Angela
Abstract: A stream of research has examined the financial well‐being of individuals. However, less research has been conducted on the financial well‐being of young adults in developing economies. To further examine this domain, we developed a conceptual framework based on the existing literature of consumer research and financial well‐being and assessed how financial literacy, socialization and attitude towards money influence the financial well‐being of young adults. Two cross‐sectional surveys were conducted on 446 young adults (preliminary study n = 156; main study n = 290; mean age 22 years) in India. This study contributes to the literature by demonstrating that financial discussion with parents during childhood positively influences financial well‐being of young adults. In addition, we found that relationship between financial literacy and financial well‐being is not significant. Furthermore, the study reveals the role of attitude towards money as a strong predictor of financial well‐being. The results provide implications for educational and financial institutions and policymakers for improving the financial well‐being of young adults.